THE IMPACT OF SERVICE QUALITY, PRODUCT QUALITY AND STORE ATMOSPHERE ON CUSTOMER LOYALTY - WICAKSONO, ARY SURYO (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2017)
The purpose of this study is to determine the impact of service quality, product quality, and store atmosphere on customer loyalty of Vosco Coffee. This research is a field research, where quantitative primary data through questionnaires instrument is taken directly from the customer of Vosco Coffee. Sampling technique used is purposive sampling, part of the non-probability sampling, where samples are selected based on the consideration that the sample may release information in accordance with the needs of the research. Based on Slovin formula, the number of the samples taken in this research is 80 customers. Data processing and analysing is done by using SPSS software 23 version.SPSS output shows that the value of R-Square is 0,816, that is, 81.6% of customer loyalty is explained by service quality, product quality and store atmosphere. The remaining, 18.4% of customer loyalty is explained by other independent variables that were not considered in this study. The regression model formed is , where Y is customer loyalty, X1 is service quality, X2 is product quality and X3 is store atmosphere. The results of the data analysis and discussion shows that service quality, product quality and store atmosphere have positive and significant impact on customer loyalty. If the customers are loyal, Vosco Caffee will have double benefits, that are: the Cafe not only get regular customers, but also, will gain new customers as the result of loyal customer’s recomendation. Thus, to make Vosco Coffee able to withstand the competition that increasingly stringent in Malang town and could grow continuously and develop rapidly, management should improve the service quality, product quality and store atmosphere. It is expected that further research can show any items from each independent variables that should be priority repaired in order to achieve the customer loyalty.